Hydroxyapatite whisker / chitin whisker co-assembled liquid crystal as well as preparation method and application thereof

By treating chitin whiskers and hydroxyapatite whiskers with TEMPO oxidation or maleic anhydride, and utilizing electrostatic repulsion and spatial orientation entropy, stable hydroxyapatite whisker/chitin whisker co-assembled liquid crystals are prepared, which solves the problem of self-assembled liquid crystals being easily destroyed and achieves liquid crystal properties with high stability and biomimetic biological structure.

CN120699635APending Publication Date: 2025-09-26JINAN UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510619282.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-14
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

It is difficult to prepare stable hydroxyapatite whiskers and chitin whiskers co-assembled liquid crystals with existing technology. The liquid crystal phase formed by the self-assembly of the two is easily destroyed by external environmental interference, making it difficult to mimic the organic/inorganic composite liquid crystal structure in organisms.

Method used

Chitosan whiskers and hydroxyapatite whiskers are treated with TEMPO oxidation or maleic anhydride treatment, and hydroxyapatite whiskers/chitosan whiskers co-assembled liquid crystals are prepared through electrostatic mutual repulsion and spatial orientation entropy, and whiskers with the same charge are used for co-assembly.

Benefits of technology

The stable co-assembly of hydroxyapatite whiskers and chitin whiskers was achieved, mimicking the chiral nematic liquid crystal phase in vivo. The co-assembled liquid crystal has high stability and good repeatability of the liquid crystal phenomenon without the use of surfactants or dispersants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120699635A_ABST
    Figure CN120699635A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of nano materials, and discloses a hydroxyapatite whisker / chitin whisker co-assembled liquid crystal as well as a preparation method and application thereof. The co-assembled liquid crystal is obtained by mixing hydroxyapatite whisker liquid crystal and chitin whisker liquid crystal which have the same electrical property, performing ultrasonic homogenization treatment and further stabilizing at room temperature. In a co-assembled liquid crystal system, the preparation and long-term stability of the co-assembled liquid crystal system are realized by two whiskers with the same electrical property based on a dual-drive principle of electrostatic repulsion and spatial orientation entropy; and the co-assembled liquid crystal simulates the liquid crystal phase and the ordered organic / inorganic phase composition in the living body in the nature in the organic / inorganic phase composition and the liquid crystal state. In addition, the adopted raw materials are wide in source and low in cost, the preparation process is simple, efficient and easy to implement, and no surfactant or dispersing agent is needed to stabilize the co-assembled liquid crystal system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of nanomaterials, and in particular relates to a hydroxyapatite whisker / chitin whisker co-assembled liquid crystal and a preparation method and application thereof. Background Art

[0002] Many organisms in nature, when constructing structures such as stems, bones, teeth, and shells during their natural growth, typically leverage their biopolymers to form a tightly ordered arrangement with inorganic materials such as inorganic mineral salts or metal oxides, resulting in a layered, ordered microstructure that achieves exceptional mechanical properties, such as high stiffness and toughness. We discovered that chitin, the primary component of the shells of crustaceans such as shrimp, crabs, and insects, is green, non-toxic, biocompatible, and biodegradable. Importantly, studies have shown that acid-hydrolyzed chitin whiskers, obtained by treating chitin with acid hydrolysis, exhibit supramolecular chirality and can self-assemble into a chiral nematic liquid crystal phase with a layered, ordered Bouligand structure.

[0003] Coincidentally, hydroxyapatite is an inorganic phosphate mineral widely found in many organisms. It is also the primary inorganic component of human bone, comprising approximately 70% of the material. The tightly packed, ordered structure of hydroxyapatite nanocrystals imparts sufficient mechanical strength and toughness to teeth and bones. Research has shown that hydroxyapatite whiskers with a specific aspect ratio and charge can self-assemble in vitro to form a liquid crystal-like, ordered structure.

[0004] However, while both chitin whiskers and hydroxyapatite whiskers can stably self-assemble into a liquid crystal state under certain conditions, the process of whisker self-assembly into the liquid crystal state is metastable and easily disrupted by external environmental conditions, leading to the destruction of the self-assembled liquid crystal phase. Furthermore, the ordered liquid crystal phases found in organisms are typically organic / inorganic composites. Therefore, it is difficult to fully mimic or replicate the liquid crystal state found in organisms using a single organic or inorganic whisker self-assembled liquid crystal. To this end, we attempted to co-assemble acid-decomposed chitin whiskers with hydroxyapatite whiskers, but the strong electrostatic attraction between the two disrupted the self-assembled liquid crystal phases, causing them to precipitate, making it difficult to obtain a stable organic / inorganic whisker co-assembled liquid crystal system. Therefore, how to prepare a co-assembled liquid crystal system in which hydroxyapatite and chitin whiskers stably coexist, better mimicking the liquid crystal phases and ordered organic / inorganic composite structures found in nature, while maximally preserving the anisotropic arrangement and liquid crystal properties of the two whiskers in the co-assembled liquid crystal suspension, is an urgent problem to be solved. Summary of the Invention

[0005] The present invention aims to overcome the shortcomings and deficiencies of the prior art and has as its primary purpose to provide a method for preparing hydroxyapatite whisker / chitin whisker co-assembled liquid crystals.

[0006] Another object of the present invention is to provide a hydroxyapatite whisker / chitin whisker co-assembled liquid crystal obtained by the above preparation method.

[0007] Another object of the present invention is to provide an application of the above-mentioned hydroxyapatite whisker / chitin whisker co-assembled liquid crystal.

[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0009] A method for preparing hydroxyapatite whisker / chitin whisker co-assembled liquid crystal comprises the following steps:

[0010] (1) preparing chitosan whiskers into a chitosan whisker suspension, and ultrasonically treating the chitosan whisker suspension to obtain chitosan whisker liquid crystals;

[0011] (2) preparing hydroxyapatite whiskers into a hydroxyapatite whisker suspension, and ultrasonically treating the hydroxyapatite whisker suspension to obtain hydroxyapatite whisker liquid crystals;

[0012] (3) adding the hydroxyapatite whisker liquid crystal prepared in step (2) to the chitin whisker liquid crystal obtained in step (1) to obtain a mixed system, and then ultrasonically homogenizing the system and allowing the system to stand to obtain a co-assembled liquid crystal.

[0013] The chitin whisker liquid crystal and the hydroxyapatite whisker liquid crystal need to have the same charge at the same time, so as to utilize the electrostatic mutual repulsion and the spatial orientation entropy effect to dual-drive co-assembly.

[0014] The chitin whiskers are preferably chitin whiskers with a negative zeta potential; more preferably chitin whiskers with a zeta potential of -50 to -30 mV; further preferably chitin whiskers with a zeta potential of -45.8 to -30.5 mV; further preferably chitin whiskers with a zeta potential of -45.8 to -35.2 mV; and most preferably at least one of TEMPO (2,2,6,6-tetramethylpiperidinyl oxide) oxidized chitin whiskers and maleic anhydride chitin whiskers.

[0015] The TEMPO oxidized chitosan whiskers are preferably prepared by the following steps: dispersing chitosan powder in deionized water containing TEMPO and sodium bromide (NaBr) at 20-30° C., then dropwise adding a sodium hypochlorite (NaClO) solution to obtain a mixed solution A; then adding an alkaline solution to adjust the pH value of the reaction solution to 9.5-10.5, and stirring for reaction; after the reaction is completed, adding ethanol to the reaction solution to quench the reaction, performing solid-liquid separation on the product, and washing the obtained solid with deionized water and freeze-drying to obtain TEMPO oxidized chitosan whiskers.

[0016] The chitosan powder is preferably used in a mass ratio of 3:1 to 20:1 with respect to sodium bromide; more preferably in a mass ratio of 9:1 to 11:1 with respect to sodium bromide; and most preferably in a mass ratio of 10:1 with respect to sodium bromide.

[0017] The concentration of TEMPO in the mixed solution A is preferably 1 to 6 mmol / L, more preferably 1 to 3 mmol / L; the concentration of NaBr is 10 to 60 mmol / L, more preferably 10 to 30 mmol / L; the concentration of NaClO is 100 to 600 mmol / L, more preferably 100 to 300 mmol / L; and the molar ratio of TEMPO:NaBr:NaClO is 1:10:100.

[0018] The alkaline solution is preferably a sodium hydroxide solution; more preferably a sodium hydroxide solution with a concentration of 1 mol / L.

[0019] The pH value is preferably 10.0.

[0020] The stirring reaction time is preferably 1 to 7 hours, more preferably 3 to 6 hours.

[0021] The amount of ethanol used is preferably calculated based on its volume being 2-15% of the volume of the reaction solution.

[0022] The solid-liquid separation method is preferably centrifugation.

[0023] The centrifugal condition is preferably 10000 rpm for 10 to 15 minutes.

[0024] The maleic anhydride chitosan whiskers are preferably prepared by the following steps: heating and melting maleic anhydride at 60-80° C. to obtain a maleic anhydride melt, then adding chitosan powder and stirring evenly to form a composite suspension, and performing maleic anhydride esterification reaction under a nitrogen atmosphere; after the reaction is completed, performing solid-liquid separation on the product, and washing the obtained solid with deionized water and freeze-drying to obtain maleic anhydride chitosan whiskers.

[0025] The heating temperature is preferably 65-70°C.

[0026] The maleic anhydride is preferably used in a mass ratio of 5:1 to 30:1 to chitin powder; more preferably in a mass ratio of 18 to 22:1 to chitin powder; and most preferably in a mass ratio of 20:1 to chitin powder.

[0027] The esterification reaction is preferably carried out at 100-135° C. for 2-6 hours; more preferably at 115-120° C. for 3-5 hours.

[0028] The solid-liquid separation method is preferably centrifugation.

[0029] The centrifugal condition is preferably 10000 rpm for 10 to 15 minutes.

[0030] The chitosan whiskers described in step (1) are preferably 100 to 1000 nm in length and 10 to 50 nm in diameter; more preferably, 150 to 350 nm in length and 15 to 30 nm in diameter.

[0031] The solvent of the chitosan whisker suspension in step (1) is deionized water; preferably, the chitosan whisker suspension is prepared by adding chitosan whiskers to deionized water for ultrasonic dispersion.

[0032] The concentration of the chitosan whisker suspension in step (1) is preferably 6 to 15 wt %; more preferably 8 to 12 wt %; and most preferably 10 to 12 wt %.

[0033] The ultrasonic treatment in step (1) is preferably performed using a cell disruptor.

[0034] The ultrasonic treatment conditions in step (1) are preferably 300-500W for 1-3h; more preferably 350-450W for 1-2h.

[0035] The hydroxyapatite whiskers are preferably hydroxyapatite whiskers with a negative zeta potential; more preferably, hydroxyapatite whiskers with a zeta potential of -45 to -31 mV; further preferably, hydroxyapatite whiskers with a zeta potential of -38.6 to -33.3 mV; and most preferably, at least one of sodium citrate-stabilized hydroxyapatite whiskers and polyacrylic acid-stabilized hydroxyapatite whiskers.

[0036] The sodium citrate-stabilized hydroxyapatite whiskers are preferably prepared by the following steps: first, adding a soluble calcium salt and a soluble phosphate salt to deionized water, stirring and mixing them thoroughly to prepare a calcium salt solution and a phosphate salt solution, respectively; then, adding the sodium citrate solution obtained by fully dissolving sodium citrate in deionized water dropwise to the calcium salt solution under stirring conditions, stirring and mixing uniformly, and then adding the phosphate salt solution dropwise thereto, stirring and reacting thoroughly to obtain a precursor solution; reacting the obtained precursor solution at a high temperature of 120 to 180° C. for 3 to 24 hours; separating the obtained product into a solid-liquid state, washing the obtained solid with anhydrous ethanol and deionized water alternately, and drying to obtain sodium citrate-stabilized hydroxyapatite whiskers.

[0037] The soluble calcium salt is preferably at least one of calcium nitrate and calcium chloride.

[0038] The concentration of the calcium salt solution is preferably 0.1 to 2 mol / L; more preferably 0.667 to 1.334 mol / L.

[0039] The soluble phosphate salt is preferably at least one of trisodium phosphate and potassium phosphate.

[0040] The concentration of the phosphate solution is preferably 0.1 to 1 mol / L; more preferably 0.4 to 0.8 mol / L.

[0041] The molar ratio of calcium to phosphorus in the precursor solution is 1.67.

[0042] The concentration of the sodium citrate solution is preferably 0.1 to 2 mol / L; more preferably 0.75 to 1.5 mol / L.

[0043] The molar ratio of the sodium citrate to the soluble calcium salt is preferably 1:6 to 4:3; more preferably 2:3 to 3:4.

[0044] The high temperature reaction conditions are preferably 150-160° C. for 6-12 hours.

[0045] The solid-liquid separation method is preferably centrifugation.

[0046] The centrifugal condition is preferably 10000 rpm for 10 to 15 minutes.

[0047] The number of washings is preferably 2 to 3 times.

[0048] The drying method is preferably vacuum drying; more preferably vacuum drying at 50-70°C.

[0049] The polyacrylic acid-stabilized hydroxyapatite whiskers are preferably prepared by the following steps: adding polyacrylic acid to a soluble calcium salt aqueous solution, mixing and stirring the calcium salt aqueous solution containing the polyacrylic acid with an equal volume of a soluble phosphate salt aqueous solution to obtain a mixed solution B, wherein the calcium-phosphorus molar ratio in the mixed solution B is controlled to be 1.67; then reacting the mixed solution B at 40-80° C. for 24-72 hours, performing solid-liquid separation, washing the obtained solid with anhydrous ethanol and deionized water alternately, and drying the obtained product to obtain polyacrylic acid-stabilized hydroxyapatite whiskers.

[0050] The soluble calcium salt is preferably at least one of calcium nitrate and calcium chloride.

[0051] The concentration of the calcium salt solution is preferably 0.05 to 2 mol / L; more preferably 0.05 to 0.2 mol / L; and most preferably 0.1 to 0.15 mol / L.

[0052] The soluble phosphate salt is preferably at least one of trisodium phosphate and potassium phosphate.

[0053] The concentration of the soluble phosphate aqueous solution is 0.05 to 2 mol / L, more preferably 0.05 to 0.2 mol / L, and most preferably 0.06 to 0.09 mol / L.

[0054] The molecular weight of the polyacrylic acid is 1500 to 3000, preferably 2000;

[0055] The molar ratio of the polyacrylic acid to the soluble calcium salt is 0.036:1 to 0.144:1, preferably 0.064:1 to 0.072:1.

[0056] The concentration of polyacrylic acid in the mixed solution B is 0.36-1.44% by mass to volume; more preferably 0.36-0.54% by mass to volume; when the mass is g, the volume is mL.

[0057] The reaction conditions of the mixed solution B are preferably 60-70° C. for 48-56 hours.

[0058] The solid-liquid separation method is preferably centrifugation.

[0059] The centrifugal condition is preferably 10000 rpm for 10 to 15 minutes.

[0060] The number of washings is preferably 2 to 3 times.

[0061] The drying method is preferably vacuum drying; more preferably vacuum drying at 50-70°C.

[0062] The hydroxyapatite whiskers described in step (2) preferably have a length of 20 to 360 nm and a diameter of 4 to 30 nm, more preferably, a length of 45 to 120 nm and a diameter of 4 to 30 nm.

[0063] The solvent of the hydroxyapatite whisker suspension in step (2) is deionized water; preferably, the suspension is prepared by adding hydroxyapatite whiskers to deionized water and ultrasonically dispersing the suspension.

[0064] The mass fraction of the hydroxyapatite whisker suspension in step (2) is preferably 10 to 60 wt %; more preferably 10 to 45 wt %.

[0065] The ultrasonic treatment in step (2) is preferably performed using a cell disruptor.

[0066] The ultrasonic treatment conditions in step (2) are preferably ultrasonic treatment at a power of 100 to 400 W for 3 to 30 min; more preferably ultrasonic treatment at a power of 200 to 250 W for 8 to 10 min.

[0067] The hydroxyapatite whisker liquid crystal and the chitin whisker liquid crystal described in step (3) are preferably mixed in a mass ratio of 1:30 to 30:1; more preferably in a mass ratio of 1:4 to 20:1.

[0068] The ultrasonic homogenization treatment conditions described in step (3) are preferably 150-400W for 15 minutes to 2 hours; more preferably 250-300W for 20 minutes.

[0069] A hydroxyapatite whisker / chitin whisker co-assembled liquid crystal is prepared by the above preparation method.

[0070] The above-mentioned hydroxyapatite whisker / chitin whisker co-assembled liquid crystal is used as a biomimetic material.

[0071] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0072] (1) The present invention uses TEMPO-oxidized chitosan whiskers or maleic anhydride-treated chitosan whiskers to co-assemble with hydroxyapatite whiskers, and utilizes a co-assembly technology driven by electrostatic mutual repulsion and spatial orientation entropy to achieve the preparation of a co-assembled liquid crystal system of the two whiskers.

[0073] (2) The hydroxyapatite whisker / chitin whisker composite system prepared by the present invention can biomimetic self-assemble to form a chiral nematic liquid crystal phase that is commonly found in organisms. Moreover, the co-assembled liquid crystal has high stability and good repeatability of the liquid crystal phenomenon.

[0074] (3) The present invention takes a multi-angle bionic approach and obtains a new type of hydroxyapatite whisker / chitin whisker co-assembled liquid crystal that has never been reported. This is more consistent with the fact that many high-strength and tough structural materials existing in nature have liquid crystal properties in their microstructure and are composed of organic and inorganic phases. It provides new ideas for the preparation and development of new organic / inorganic bionic functional materials.

[0075] (4) The raw materials used in the present invention are widely available, low in cost, and have a simple and efficient preparation process. In addition, no surfactant or dispersant is required to stabilize the co-assembled liquid crystal system. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 TEM morphology photos of different whiskers; among them, A is the TEMPO-oxidized chitin whisker in Example 1, B is the sodium citrate-stabilized hydroxyapatite whisker in Example 1, and C is the maleic anhydride-stabilized chitin whisker in Example 2.

[0077] Figure 2 1 and 2. These are the zeta potential diagrams of the TEMPO-oxidized chitin whiskers in Example 1, the acid-decomposed chitin whiskers in Comparative Example 1, the maleic anhydride-treated chitin whiskers in Example 2, and the sodium citrate-stabilized hydroxyapatite whiskers in Example 1.

[0078] Figure 3 These are actual photographs of the Tyndall effect of different whisker co-assembled liquid crystal systems; wherein, A is the hydroxyapatite whisker / TEMPO-oxidized chitosan whisker co-assembled liquid crystal in Example 1, B is the hydroxyapatite whisker / acid-decomposed chitosan whisker co-assembled liquid crystal in Comparative Example 1, and C is the maleic anhydride chitosan whisker / hydroxyapatite whisker co-assembled liquid crystal in Example 2.

[0079] Figure 4 Polarized microscope photographs of different whisker co-assembled liquid crystal systems; wherein A is the hydroxyapatite whisker / TEMPO-oxidized chitosan whisker co-assembled liquid crystal in Example 1, B is the acid-decomposed chitosan whisker / hydroxyapatite co-assembled liquid crystal in Comparative Example 1, and C is the hydroxyapatite whisker / maleic anhydride chitosan whisker in Example 6.

[0080] Figure 5 Polarized microscope photographs of different whisker self-assembled liquid crystals; wherein A is the TEMPO-oxidized chitin whisker liquid crystal in Example 3, B is the acid-decomposed chitin whisker liquid crystal in Comparative Example 1, C is the maleic anhydride chitin whisker liquid crystal in Example 2, and D is the sodium citrate-stabilized hydroxyapatite whisker liquid crystal in Example 3.

[0081] Figure 6Polarized microscope photographs of hydroxyapatite whiskers / TEMPO oxidized chitin whiskers co-assembled liquid crystals with different mass ratios; wherein A is the co-assembled liquid crystal in Example 3, B is the co-assembled liquid crystal in Example 4, C is the co-assembled liquid crystal in Example 5, and D is the co-assembled liquid crystal in Example 7.

[0082] Figure 7 This is a graph showing the frequency sweep results of the acid-decomposed chitosan whisker liquid crystal CHWs in Comparative Example 1, the hydroxyapatite whisker liquid crystal HAp in Example 3, and the hydroxyapatite whisker / TEMPO-oxidized chitosan whisker co-assembled liquid crystal in Example 5 under a rotational rheometer.

[0083] Figure 8 Figure 1 is a photo of the film (A) and a tensile strength test result diagram; wherein, CHWs is the acid-decomposed chitin whisker liquid crystal film in Comparative Example 1, HAp is the hydroxyapatite whisker liquid crystal film in Example 3, and HAp / T-CHWs is the hydroxyapatite whisker / TEMPO-oxidized chitin whisker co-assembled liquid crystal in Example 5. DETAILED DESCRIPTION

[0084] The present invention is further described below with reference to specific examples. Unless otherwise specified, all raw materials and reagents in the present invention are commercially available raw materials and reagents.

[0085] The present invention is described in detail below with specific examples.

[0086] Example 1

[0087] (1) Preparation of TEMPO-oxidized chitosan whisker liquid crystals: 3 g of chitosan powder was dispersed in 90 mL of deionized water containing 0.048 g of TEMPO and 0.3 g of NaBr at 23°C, and then 10 mL of NaClO solution (active chlorine content: 10%) was added dropwise to obtain a mixed solution; wherein the concentration of TEMPO was 3 mmol / L, the concentration of NaBr was 30 mmol / L, and the concentration of NaClO was 300 mmol / L, and the molar ratio of TEMPO:NaBr:NaClO in the mixed solution was 1:10:100. 1 mol / L sodium hydroxide solution was then added to adjust the reaction pH to 10.0, and the reaction was stirred for 3 h. After the reaction was completed, 10-15 mL of ethanol was added to the reaction solution to quench the reaction. The product was centrifuged at 10,000 rpm for 10 min, washed with deionized water, and freeze-dried to obtain TEMPO-oxidized chitosan whiskers. The obtained TEMPO oxidized chitosan whiskers were then dispersed in deionized water to prepare a whisker suspension with a concentration of 10 wt %. Finally, the suspension was ultrasonically treated at a power of 400 W for 1 h using a cell disruptor to obtain TEMPO oxidized chitosan whisker liquid crystals.

[0088] (2) Preparation of sodium citrate-stabilized hydroxyapatite whisker liquid crystals: 2.36 g (10 mmol) of calcium nitrate tetrahydrate and 2.28 g (6 mmol) of trisodium phosphate dodecahydrate were added to 15 mL of deionized water at a calcium-phosphorus molar ratio of 1.67, and stirred and mixed thoroughly to prepare calcium salt solution and phosphate salt solution, respectively. The concentration of the calcium nitrate solution was 0.667 mol / L, and the concentration of the trisodium phosphate solution was 0.4 mol / L. Then, 2.20 g (7.5 mmol) of sodium citrate was added to 10 mL of deionized water. After the dihydrate is fully dissolved, the resulting sodium citrate solution with a concentration of 0.75 mol / L is added dropwise to the calcium salt solution under stirring, stirred for 10 minutes to mix evenly, and then the phosphate salt solution is added dropwise thereto and stirred for 10 minutes to fully react; the resulting precursor solution is reacted in a high-temperature reactor at 150°C for 12 hours, and the resulting product is then centrifuged at 10,000 rpm for 10 minutes, the precipitate is taken, and washed alternately with anhydrous ethanol and deionized water three times, followed by vacuum drying at 60°C to obtain sodium citrate-stabilized hydroxyapatite whiskers. The obtained sodium citrate-stabilized hydroxyapatite whiskers are then dispersed in deionized water to prepare a whisker suspension with a mass fraction of 40 wt%, and finally ultrasonically treated with a cell disruptor at 200 W power for 8 minutes to obtain sodium citrate-stabilized hydroxyapatite whisker liquid crystals.

[0089] (3) The hydroxyapatite whisker liquid crystal prepared in step (2) is added to the chitin whisker liquid crystal obtained in step (1) at a mass ratio of 20:1 to obtain a mixed system, and then ultrasonically homogenized at a power of 250 W using a cell disruptor for 40 minutes, and placed at room temperature for further stabilization to obtain a co-assembled liquid crystal.

[0090] The TEMPO-oxidized chitosan whiskers prepared in step (1) were observed by transmission electron microscopy. Figure 1 As shown in A in FIG, the chitin whiskers obtained by the above steps are needle-shaped, and their length and diameter are mainly concentrated in the range of 150-350 nm and 15-30 nm, respectively, with a high aspect ratio. Similarly, the sodium citrate-stabilized hydroxyapatite whiskers prepared in step (2) were observed by transmission electron microscopy, and the results are shown in FIG. Figure 1 As shown in Figure B, the hydroxyapatite whiskers obtained through the above steps are in the form of thin rods, with lengths and diameters mainly concentrated in the range of 45-60 nm and 4-8 nm, respectively, and have a high aspect ratio. The zeta potential values ​​of TEMPO-oxidized chitin whiskers and sodium citrate-stabilized hydroxyapatite whiskers were measured by a Zeta potential analyzer. The results are shown in Figure 4. Figure 2As shown, the TEMPO-oxidized chitin whiskers were negatively charged after oxidation and had a zeta potential of -43.1 mV. The zeta potential of the sodium citrate-stabilized hydroxyapatite whiskers was also negatively charged, with a zeta potential of -34.3 mV.

[0091] from Figure 3 A in FIG shows that the two negatively charged whiskers co-assembled liquid crystals obtained in step (3) have good dispersion, the laser can pass through well, and no flocculation occurs. The co-assembled liquid crystals obtained in step (3) were observed by polarizing microscopy. The TEMPO oxidized chitin whiskers have a high negative charge due to the presence of a large number of carboxyl groups on their surface, and due to the electrostatic mutual repulsion, they can be well and stably dispersed with the hydroxyapatite whiskers with the same negative charge on the surface, thereby achieving stable co-assembly of the two whiskers. The polarizing microscope shows the good liquid crystal fingerprint texture of the co-assembled liquid crystal. The results are shown in FIG. Figure 4 As shown in A.

[0092] Comparative Example 1:

[0093] (1) According to the literature (Liu W, Liu K, Zhu L, et al. Liquid crystalline andrheological properties of chitin whiskers with different chemical structures and chargeability [J]. International Journal of Biological Macromolecules, 2020, 157: 24-35.), positively charged acid-decomposed chitin whiskers were prepared by conventional acid decomposition method. Then, a 10 wt% whisker suspension was prepared in the same manner, and the suspension was ultrasonically homogenized for 2 h at 400 W using a cell disruptor to obtain acid-decomposed chitin whisker liquid crystals. The acid-decomposed chitin whisker liquid crystal suspension was cast on a polytetrafluoroethylene mold and naturally evaporated for 24 h to obtain an acid-decomposed chitin whisker liquid crystal film.

[0094] (2) Sodium citrate-stabilized hydroxyapatite whiskers were prepared according to the method of step (2) of Example 1 to prepare a whisker suspension with a mass fraction of 40 wt%, and sodium citrate-stabilized hydroxyapatite whisker liquid crystals.

[0095] (3) The hydroxyapatite whisker liquid crystal prepared in step (2) was then added to the acid-decomposed chitin whisker liquid crystal prepared in step (1) at a mass ratio of 20:1 to obtain a mixed system, which was then ultrasonically homogenized at 250 W for 40 min using a cell disruptor and further stabilized at room temperature to obtain a co-assembled system.

[0096] The acid-decomposed chitin whiskers prepared in step (1) were observed under a transmission electron microscope. The length and diameter of the chitin whiskers were mainly concentrated in the range of 250 to 750 nm and 18 to 35 nm, respectively, and had a high aspect ratio. The hydroxyapatite whiskers prepared in step (2) were observed under a transmission electron microscope. The length and diameter of the chitin whiskers were mainly concentrated in the range of 45 to 60 nm and 4 to 8 nm, respectively, and had a relatively high aspect ratio.

[0097] The zeta potential value of the acid-decomposed chitosan whiskers was measured by a Zeta potential analyzer. Figure 2 As shown, the acid-decomposed chitosan whiskers were positively charged and had a zeta potential of +18.8 mV.

[0098] from Figure 3 In B, we can see that the co-assembly system of whiskers with opposite charges obtained in step (3) has poor dispersion, the laser cannot penetrate, and the flocculation phenomenon is more obvious.

[0099] The acid-decomposed chitosan whisker system prepared in step (1) was observed by polarizing microscope. Figure 5 As shown in B, it shows that the acid-decomposed chitosan whiskers can self-assemble to form a liquid crystal phase, showing good liquid crystal fingerprint texture characteristics under polarized light. It can be seen from Example 1 and the comparative example that although both chitosan whiskers and hydroxyapatite whiskers can self-assemble to form liquid crystals, we observed the co-assembly system prepared in step (3) through a polarizing microscope ( Figure 4 B) in the figure shows that since the positive charge on the surface of the acid-hydrolyzed chitosan whiskers is opposite to the negative charge on the surface of the hydroxyapatite whiskers, the two whiskers attract each other due to electrostatic force, which destroys the original self-assembly behavior of the whiskers, causing the colloidal solution system to be unstable and then flocculate, resulting in no birefringence.

[0100] The frequency of the acid-decomposed chitosan whisker liquid crystal prepared by step (1) in the comparative example 1 was scanned by a rotational rheometer. The results are as follows: Figure 7 As shown in the figure, the storage modulus (G') of the acid-decomposed chitosan whisker liquid crystal is greater than the loss modulus (G"), which shows the behavior of elastic gel.

[0101] After 24 hours of natural evaporation, the obtained acid-decomposed chitosan whisker liquid crystal film was immersed in water for 2 hours, and it was found that its morphology could not be stabilized. Figure 8 As shown in A. The acid-decomposed chitosan whisker liquid crystal film obtained in step (1) was further subjected to a tensile test by a tensile testing machine. The results are shown in FIG. Figure 8 As shown in Figure B, the tensile strength of the acid-decomposed chitosan whisker liquid crystal film is 521 kPa.

[0102] Example 2

[0103] () Preparation of maleic anhydride chitosan whiskers: 100 g of maleic anhydride was melted at 65° C. to obtain a maleic anhydride melt, followed by addition of 5 g of chitosan powder and stirring to form a composite suspension, which was then subjected to maleic anhydride esterification reaction at 120° C. under a nitrogen atmosphere for 3 h. After the reaction, the product was centrifuged at 10,000 rpm for 10 min, washed with deionized water, and freeze-dried to obtain maleic anhydride chitosan whiskers. The obtained maleic anhydride chitosan whiskers were then dispersed in deionized water to prepare a whisker suspension with a concentration of 10 wt%. Finally, the suspension was ultrasonically treated at 400 W for 2 h using a cell disruptor to obtain maleic anhydride chitosan whisker liquid crystals.

[0104] (2) Preparation of sodium citrate-stabilized hydroxyapatite whisker liquid crystals: 2.36 g (10 mmol) of calcium nitrate tetrahydrate and 2.28 g (6 mmol) of trisodium phosphate dodecahydrate were added to 15 mL of deionized water at a calcium-phosphorus molar ratio of 1.67, and stirred and mixed thoroughly to prepare calcium salt solution and phosphate salt solution, respectively. The concentration of the calcium nitrate solution was 0.667 mol / L, and the concentration of the trisodium phosphate solution was 0.4 mol / L. Then, 2.20 g (7.5 mmol) of sodium citrate was added to 10 mL of deionized water. After the sodium citrate dihydrate is fully dissolved, a sodium citrate solution with a concentration of 0.75 mol / L is added dropwise to the calcium salt solution under stirring, stirred for 10 minutes to mix evenly, and then a phosphate salt solution is added dropwise thereto and stirred for 10 minutes to fully react; the resulting precursor solution is reacted in a high-temperature reactor at 150°C for 12 hours, and then the obtained product is centrifuged at 10,000 rpm for 10 minutes, the precipitate is taken, and washed alternately with anhydrous ethanol and deionized water three times, and vacuum dried at 60°C to obtain sodium citrate-stabilized hydroxyapatite whiskers. Then, the obtained sodium citrate-stabilized hydroxyapatite whiskers are dispersed in deionized water to prepare a whisker suspension with a mass fraction of 45wt%, and finally ultrasonically treated with a cell disruptor at a power of 200W for 10 minutes to obtain sodium citrate-stabilized hydroxyapatite whisker liquid crystals.

[0105] (3) The hydroxyapatite whisker liquid crystal prepared in step (2) is added to the chitin whisker liquid crystal obtained in step (1) at a mass ratio of 20:1 to obtain a mixed system, and then ultrasonically homogenized at a power of 250 W using a cell disruptor for 40 minutes, and further stabilized at room temperature to obtain a co-assembled liquid crystal.

[0106] The morphology of the maleic anhydride chitosan whiskers prepared in step (1) was observed by transmission electron microscopy. Figure 1As shown in Figure C, the maleic anhydride chitosan whiskers obtained in the above steps are needle-shaped, with lengths and diameters mainly concentrated in the range of 150-300 nm and 15-20 nm, respectively, and have a high aspect ratio. Observation of the hydroxyapatite whiskers prepared in step (2) shows that their lengths and diameters are mainly concentrated in the range of 45-60 nm and 4-8 nm, respectively, and have a high aspect ratio.

[0107] The zeta potential of maleic anhydride chitosan whiskers was measured by Zeta potential analyzer. Figure 2 As shown, the maleic anhydride chitosan whiskers are negatively charged and have a zeta potential of -35.2 mV, while the zeta potential of the sodium citrate-stabilized hydroxyapatite whiskers is -34.3 mV.

[0108] from Figure 3 As can be seen from C in FIG, the two negatively charged whiskers obtained in step (3) have good dispersion in the co-assembled liquid crystal, and the laser can pass through well without obvious flocculation.

[0109] The maleic anhydride chitosan whisker liquid crystal obtained in step (1) was observed by polarizing microscope. Figure 5 As shown in C, it shows that maleic anhydride chitosan whiskers can self-assemble to form a liquid crystal phase, which has obvious liquid crystal fingerprint texture characteristics under polarized light.

[0110] Example 3

[0111] (1) Preparation of TEMPO-oxidized chitosan whisker liquid crystals: 6 g of chitosan powder was dispersed in 180 mL of deionized water containing 0.096 g of TEMPO and 0.6 g of NaBr at 28°C, and then 20 mL of NaClO solution (active chlorine content: 10%) was added dropwise to obtain a mixed solution; wherein the concentration of TEMPO was 3 mmol / L, the concentration of NaBr was 30 mmol / L, and the concentration of NaClO was 300 mmol / L, and the molar ratio of TEMPO:NaBr:NaClO in the mixed solution was 1:10:100. A 1 mol / L sodium hydroxide solution was continuously added to adjust the reaction pH to 10.0, and the reaction was stirred for 4 hours. After the reaction was completed, 10 to 15 mL of ethanol was added to the reaction solution to quench the reaction. The product was centrifuged at 10,000 rpm for 10 minutes, washed with deionized water, and freeze-dried to obtain TEMPO-oxidized chitosan whiskers. The obtained TEMPO-oxidized chitosan whiskers were then dispersed in deionized water to prepare a whisker suspension with a concentration of 10 wt%. Finally, the suspension was ultrasonically treated with a cell disruptor at a power of 400 W for 2 hours to obtain TEMPO-oxidized chitosan whisker liquid crystals.

[0112] (2) Preparation of sodium citrate-stabilized hydroxyapatite whisker liquid crystals: 4.72 g (20 mmol) of calcium nitrate tetrahydrate and 4.56 g (12 mmol) of trisodium phosphate dodecahydrate were added to 15 mL of deionized water at a calcium-to-phosphorus molar ratio of 1.67, and stirred and mixed thoroughly to prepare calcium salt solution and phosphate salt solution, respectively. The concentration of the calcium nitrate solution was 1.334 mol / L, and the concentration of the trisodium phosphate solution was 0.8 mol / L. Then, 4.40 g (15 mmol) of sodium citrate dihydrate was fully dissolved in 10 mL of deionized water to obtain a sodium citrate solution with a concentration of 1.5 mol / L, which was then added dropwise to the calcium salt solution under stirring. The mixture was stirred for 10 minutes to mix evenly, and then a phosphate solution was added dropwise and stirred for 10 minutes to fully react. The resulting precursor solution was reacted in a high-temperature reactor at 150°C for 8 hours, and the resulting product was centrifuged at 10,000 rpm for 10 minutes. The precipitate was washed three times alternately with anhydrous ethanol and deionized water, and vacuum-dried at 60°C to obtain sodium citrate-stabilized hydroxyapatite whiskers. The obtained sodium citrate-stabilized hydroxyapatite whiskers were dispersed in deionized water to prepare a whisker suspension with a mass fraction of 40 wt%. Finally, a cell disruptor was ultrasonically treated at 200 W for 10 minutes to obtain sodium citrate-stabilized hydroxyapatite whisker liquid crystals. The hydroxyapatite whisker liquid crystal suspension was cast into a polytetrafluoroethylene mold and naturally evaporated for 24 hours to obtain a hydroxyapatite whisker liquid crystal film.

[0113] (3) The hydroxyapatite whisker liquid crystal prepared in step (2) is added to the chitin whisker liquid crystal obtained in step (1) at a mass ratio of 20:1 to obtain a mixed system, and then ultrasonically homogenized at a power of 250 W using a cell disruptor for 40 minutes, and further stabilized at room temperature to obtain a co-assembled liquid crystal.

[0114] The TEMPO oxidized chitosan whiskers prepared in step (1) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 150 to 350 nm and 15 to 30 nm, respectively, and had a high aspect ratio. The hydroxyapatite whiskers prepared in step (2) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 45 to 60 nm and 4 to 8 nm, respectively, and had a relatively high aspect ratio.

[0115] The zeta potential values ​​of the TEMPO-oxidized chitosan whiskers and sodium citrate-stabilized hydroxyapatite whiskers prepared in the above steps were measured by a Zeta potential analyzer, and were -44.8 mV and -38.6 mV, respectively.

[0116] The TEMPO oxidized chitosan whisker liquid crystal obtained in step (1) was observed by polarizing microscope. Figure 5As shown in A; The sodium citrate-stabilized hydroxyapatite whisker liquid crystal obtained in step (2) was observed by polarizing microscope, and the results were as follows Figure 5 The results show that both exhibit birefringence and obvious fingerprint texture, indicating that both whiskers can form a well-ordered liquid crystal structure through self-assembly.

[0117] The co-assembled liquid crystal prepared in step (3) was observed by polarizing microscope. Due to the electrostatic mutual repulsion, the two whiskers can be well and stably dispersed in the water phase, realizing the co-assembly of the two whiskers. The polarizing microscope showed the good liquid crystal fingerprint texture of the co-assembled liquid crystal. The results are as follows: Figure 6 As shown in A.

[0118] The hydroxyapatite whisker liquid crystal prepared in step (2) was subjected to frequency scanning by a rotational rheometer. The results are as follows: Figure 7 As shown, the storage modulus (G') of hydroxyapatite whisker liquid crystal is greater than the loss modulus (G"), showing the behavior of elastic gel.

[0119] After 24 hours of natural evaporation, the sodium citrate-stabilized hydroxyapatite whisker liquid crystal suspension could not form a film due to its excessive brittleness.

[0120] Example 4

[0121] (1) Preparation of TEMPO-oxidized chitosan whisker liquid crystals: 3 g of chitosan powder was dispersed in 290 mL of deionized water containing 0.048 g of TEMPO and 0.3 g of NaBr at 26°C, and then 10 mL of NaClO solution (active chlorine content: 10%) was added dropwise to obtain a mixed solution; wherein the concentration of TEMPO was 1 mmol / L, the concentration of NaBr was 10 mmol / L, and the concentration of NaClO was 100 mmol / L, and the molar ratio of TEMPO:NaBr:NaClO in the mixed solution was 1:10:100. A 1 mol / L sodium hydroxide solution was continuously added to adjust the reaction pH to 10.0, and the reaction was stirred for 4 hours. After the reaction was completed, 10 to 15 mL of ethanol was added to the reaction solution to quench the reaction. The product was centrifuged at 10,000 rpm for 10 minutes, washed with deionized water, and freeze-dried to obtain TEMPO-oxidized chitosan whiskers. The obtained TEMPO-oxidized chitosan whiskers were then dispersed in deionized water to prepare a whisker suspension with a concentration of 10 wt%. Finally, the suspension was ultrasonically treated with a cell disruptor at a power of 400 W for 2 hours to obtain TEMPO-oxidized chitosan whisker liquid crystals.

[0122] (2) Preparation of sodium citrate-stabilized hydroxyapatite whisker liquid crystals: 4.72 g (20 mmol) of calcium nitrate tetrahydrate and 4.56 g (12 mmol) of trisodium phosphate dodecahydrate were added to 15 mL of deionized water at a calcium-phosphorus molar ratio of 1.67, and stirred and mixed thoroughly to prepare calcium salt solution and phosphate salt solution, respectively. The concentration of the calcium nitrate solution was 1.334 mol / L, and the concentration of the trisodium phosphate solution was 0.8 mol / L. Then, 3.92 g (13.3 mmol) of sodium citrate dihydrate was fully dissolved in 10 mL of deionized water to obtain a sodium citrate solution with a concentration of 1.33 mol / L, which was then added dropwise to the calcium salt solution under stirring. The mixture was stirred for 10 minutes to mix evenly, and then a phosphate solution was added dropwise thereto and stirred for 10 minutes to fully react; the obtained precursor solution was reacted in a high-temperature reactor at 150° C. for 6 hours, and then the obtained product was centrifuged at 10,000 rpm for 10 minutes, the precipitate was taken, and washed alternately with anhydrous ethanol and deionized water for 3 times, and vacuum-dried at 60° C. to obtain sodium citrate-stabilized hydroxyapatite whiskers, and the obtained sodium citrate-stabilized hydroxyapatite whiskers were dispersed in deionized water to prepare a whisker suspension with a mass fraction of 45wt%, and finally a cell disruptor was used to perform ultrasonic treatment at a power of 250W for 10 minutes to obtain sodium citrate-stabilized hydroxyapatite whisker liquid crystals.

[0123] (3) The hydroxyapatite whisker liquid crystal prepared in step (2) is added to the chitin whisker liquid crystal obtained in step (1) at a mass ratio of 15:1 to obtain a mixed system, and then ultrasonically homogenized for 35 minutes at a power of 250 W using a cell disruptor, and further stabilized at room temperature to obtain a co-assembled liquid crystal.

[0124] The TEMPO oxidized chitosan whiskers prepared in step (1) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 150-350 nm and 15-30 nm, respectively, and had a high aspect ratio. The hydroxyapatite whiskers prepared in step (2) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 45-60 nm and 4-8 nm, respectively, and had a relatively high aspect ratio.

[0125] The zeta potential value of the TEMPO oxidized chitosan whiskers prepared in the above steps was measured by a Zeta potential analyzer: -44.5 mV, and the zeta potential value of the sodium citrate stabilized hydroxyapatite whiskers was: -33.3 mV.

[0126] The co-assembled liquid crystal prepared in step (3) was observed by polarizing microscope. Due to the electrostatic mutual repulsion, the two whiskers can be well and stably dispersed in the water phase, realizing the co-assembly of the two whiskers. The polarizing microscope showed the good liquid crystal fingerprint texture of the co-assembled liquid crystal. The results are as follows: Figure 6 As shown in B.

[0127] Example 5

[0128] (1) Preparation of TEMPO-oxidized chitosan whisker liquid crystals: 6 g of chitosan was dispersed in 580 mL of deionized water containing 0.096 g of TEMPO and 0.6 g of NaBr at 24°C, and then 20 mL of NaClO solution (active chlorine content: 10%) was added dropwise to obtain a mixed solution; wherein the concentration of TEMPO was 1 mmol / L, the concentration of NaBr was 10 mmol / L, and the concentration of NaClO was 100 mmol / L, and the molar ratio of TEMPO:NaBr:NaClO in the mixed solution was 1:10:100. A 1 mol / L sodium hydroxide solution was continuously added to adjust the reaction pH to 10.0, and the reaction was stirred for 6 hours. After the reaction was completed, 10 to 15 mL of ethanol was added to the reaction solution to quench the reaction. The product was centrifuged at 10,000 rpm for 10 minutes, washed with deionized water, and freeze-dried to obtain TEMPO-oxidized chitosan whiskers. The obtained TEMPO-oxidized chitosan whiskers were then dispersed in deionized water to prepare a whisker suspension with a concentration of 10 wt%. Finally, the suspension was ultrasonically treated with a cell disruptor at a power of 350 W for 1 hour to obtain TEMPO-oxidized chitosan whisker liquid crystals.

[0129] (2) Preparation of sodium citrate-stabilized hydroxyapatite whisker liquid crystals: 2.36 g (10 mmol) of calcium nitrate tetrahydrate and 2.28 g (6 mmol) of trisodium phosphate dodecahydrate were added to 15 mL of deionized water at a calcium-phosphorus molar ratio of 1.67, and stirred and mixed thoroughly to prepare calcium salt solution and phosphate salt solution, respectively. The concentration of the calcium nitrate solution was 0.667 mol / L, and the concentration of the trisodium phosphate solution was 0.4 mol / L. Then, 2.20 g (7.5 mmol) of sodium citrate dihydrate was fully dissolved in 10 mL of deionized water to obtain a sodium citrate solution with a concentration of 0.75 mol / L, which was added dropwise to the calcium salt solution under stirring. , stirring for 10 minutes to mix evenly, then adding phosphate solution dropwise thereto, stirring for 10 minutes to fully react, and finally reacting the obtained precursor solution in a high-temperature reactor at 150°C for 12 hours; the obtained product was centrifuged at 10000 rpm for 10 minutes, taking the precipitate, and washing it alternately with anhydrous ethanol and deionized water for 3 times, and vacuum drying at 60°C to obtain sodium citrate-stabilized hydroxyapatite whiskers, and the obtained sodium citrate-stabilized hydroxyapatite whiskers were dispersed in deionized water to prepare a whisker suspension with a mass fraction of 40wt%, and finally ultrasonically treated with a cell disruptor at a power of 200W for 10 minutes to obtain sodium citrate-stabilized hydroxyapatite whisker liquid crystals.

[0130] (3) The hydroxyapatite whisker liquid crystal prepared in step (2) was added to the chitin whisker liquid crystal obtained in step (1) at a mass ratio of 10:1 to obtain a mixed system, and then ultrasonically homogenized at 300 W for 25 minutes using a cell disruptor, and further stabilized at room temperature to obtain a co-assembled liquid crystal. The co-assembled liquid crystal suspension was cast on a polytetrafluoroethylene mold and naturally evaporated for 24 hours to obtain a co-assembled liquid crystal film.

[0131] The TEMPO oxidized chitosan whiskers prepared in step (1) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 150-350 nm and 15-30 nm, respectively, and had a high aspect ratio. The hydroxyapatite whiskers prepared in step (2) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 45-60 nm and 4-8 nm, respectively, and had a relatively high aspect ratio.

[0132] The zeta potential value of the TEMPO oxidized chitosan whiskers prepared in the above steps was measured by a Zeta potential analyzer: -45.8 mV, and the zeta potential value of the sodium citrate stabilized hydroxyapatite whiskers was: -35.1 mV.

[0133] The co-assembled liquid crystal prepared in step (3) was observed by polarizing microscope. Due to the electrostatic mutual repulsion, the two whiskers can be well and stably dispersed in the water phase, realizing the co-assembly of the two whiskers. The polarizing microscope showed the good liquid crystal fingerprint texture of the co-assembled liquid crystal. The results are as follows: Figure 6 As shown in C.

[0134] The co-assembled liquid crystal prepared in step (3) was subjected to frequency scanning by a rotational rheometer. The results are as follows: Figure 7 As shown, the storage modulus (G') of the co-assembled liquid crystal is greater than the loss modulus (G"), showing the behavior of an elastic gel. Moreover, based on the strong electrostatic repulsion between the two negatively charged whiskers, the modulus of the co-assembled liquid crystal system far exceeds that of the corresponding single whisker liquid crystal system.

[0135] After 24 hours of natural evaporation, the co-assembled liquid crystal film was immersed in water for 2 hours, and its morphology was found to be well maintained. Figure 8 As shown in A. The co-assembled liquid crystal film obtained in step (3) was further subjected to a tensile test by a tensile testing machine. The results are shown in FIG. Figure 8 As shown in B, the tensile strength of the co-assembled liquid crystal film is 5100 kPa, and the mechanical strength is increased by about 10 times compared with the single-component liquid crystal film.

[0136] Example 6

[0137] (1) Preparation of maleic anhydride chitosan whiskers: 100 g of maleic anhydride was melted at 70° C. to obtain a maleic anhydride melt, and then 5 g of chitosan powder was added and stirred to form a composite suspension. Maleic anhydride esterification reaction was carried out at 115° C. under a nitrogen atmosphere for 5 h. After the reaction, the product was centrifuged at 10,000 rpm for 10 min, washed with deionized water, and freeze-dried to obtain maleic anhydride chitosan whiskers. The obtained maleic anhydride chitosan whiskers were then dispersed in deionized water to prepare a whisker suspension with a concentration of 12 wt%. Finally, the suspension was ultrasonically treated with a cell disruptor at a power of 350 W for 2 h to obtain maleic anhydride chitosan whisker liquid crystals.

[0138] (2) Preparation of sodium citrate-stabilized hydroxyapatite whisker liquid crystals: 4.72 g (20 mmol) of calcium nitrate tetrahydrate and 4.56 g (12 mmol) of trisodium phosphate dodecahydrate were added to 15 mL of deionized water at a calcium-to-phosphorus molar ratio of 1.67, and stirred and mixed thoroughly to prepare calcium salt solution and phosphate salt solution, respectively. The concentration of the calcium nitrate solution was 1.334 mol / L, and the concentration of the trisodium phosphate solution was 0.8 mol / L. Then, 4.40 g (15 mmol) of sodium citrate dihydrate was fully dissolved in 10 mL of deionized water to obtain a sodium citrate solution with a concentration of 1.5 mol / L, which was then added dropwise to the calcium salt solution under stirring. , stirred for 10 minutes to mix evenly, then added phosphate solution dropwise thereto, stirred for 10 minutes to fully react, and finally the obtained precursor solution was reacted in a high-temperature reactor at 150°C for 12 hours, and then the obtained product was centrifuged at 10000 rpm for 10 minutes, the precipitate was taken, and washed alternately with anhydrous ethanol and deionized water for 3 times, and vacuum dried at 60°C to obtain sodium citrate-stabilized hydroxyapatite whiskers, and the obtained sodium citrate-stabilized hydroxyapatite whiskers were dispersed in deionized water to prepare a whisker suspension with a mass fraction of 50wt%, and finally a cell disruptor was used to perform ultrasonic treatment at 200W power for 10 minutes to obtain sodium citrate-stabilized hydroxyapatite whisker liquid crystals.

[0139] (3) The hydroxyapatite whisker liquid crystal prepared in step (2) was added to the chitin whisker liquid crystal obtained in step (1) at a mass ratio of 5:1 to obtain a mixed system, which was then ultrasonically homogenized at a power of 300 W for 35 minutes using a cell disruptor and further stabilized at room temperature to obtain a co-assembled liquid crystal.

[0140] Transmission electron microscopy observation of the maleic anhydride chitosan whiskers prepared in step (1) showed that their length and diameter were mainly concentrated in the range of 150-300 nm and 15-20 nm, respectively, with a high aspect ratio; observation of the hydroxyapatite whiskers prepared in step (2) showed that their length and diameter were mainly concentrated in the range of 45-60 nm and 4-8 nm, respectively, with a relatively high aspect ratio.

[0141] The zeta potential value of the maleic anhydride chitosan whiskers prepared in the above steps was measured by a Zeta potential analyzer: -30.5 mV, and the zeta potential value of the sodium citrate-stabilized hydroxyapatite whiskers was: -34.8 mV.

[0142] The co-assembled liquid crystal prepared in step (3) was observed by polarizing microscope. Since both maleic anhydride chitosan whiskers and hydroxyapatite whiskers were negatively charged, the two whiskers could be co-assembled to obtain a liquid crystal phase. However, since the negative charge of maleic anhydride chitosan whiskers was lower than that of TEMPO oxidized chitosan whiskers, the stability of the co-assembled liquid crystal system of the two whiskers was not particularly ideal. Only some liquid crystal texture features could be observed under polarized light. The results are as follows: Figure 4 As shown in C.

[0143] Example 7

[0144] (1) Preparation of TEMPO-oxidized chitosan whisker liquid crystals: 3 g of chitosan powder was dispersed in 290 mL of deionized water containing 0.048 g of TEMPO and 0.3 g of NaBr at 25°C, and then 10 mL of NaClO solution (active chlorine content: 10%) was added dropwise to obtain a mixed solution; wherein the concentration of TEMPO was 1 mmol / L, the concentration of NaBr was 10 mmol / L, and the concentration of NaClO was 100 mmol / L, and the molar ratio of TEMPO:NaBr:NaClO in the mixed solution was 1:10:100. A 1 mol / L sodium hydroxide solution was continuously added to adjust the reaction pH to 10.0, and the reaction was stirred for 4 hours. After the reaction was completed, 10 to 15 mL of ethanol was added to the reaction solution to quench the reaction. The product was centrifuged at 10,000 rpm for 10 minutes, washed with deionized water, and freeze-dried to obtain TEMPO-oxidized chitosan whiskers. The obtained TEMPO-oxidized chitosan whiskers were then dispersed in deionized water to prepare a whisker suspension with a concentration of 10 wt%. Finally, the suspension was ultrasonically treated with a cell disruptor at a power of 450 W for 1 hour to obtain TEMPO-oxidized chitosan whisker liquid crystals.

[0145] (2) Preparation of sodium citrate-stabilized hydroxyapatite whisker liquid crystals: 2.36 g (10 mmol) of calcium nitrate tetrahydrate and 2.28 g (6 mmol) of trisodium phosphate dodecahydrate were added to 15 mL of deionized water at a calcium-phosphorus molar ratio of 1.67, and stirred and mixed thoroughly to prepare calcium salt solution and phosphate salt solution, respectively. The concentration of the calcium nitrate solution was 0.667 mol / L, and the concentration of the trisodium phosphate solution was 0.4 mol / L. Then, 2.20 g (7.5 mmol) of sodium citrate dihydrate was fully dissolved in 10 mL of deionized water to obtain a sodium citrate solution with a concentration of 0.75 mol / L. The solution was added dropwise to the calcium salt solution under stirring. The mixture was stirred for 10 minutes to mix evenly, and then a phosphate solution was added dropwise thereto, stirred for 10 minutes to fully react, and finally the obtained precursor solution was reacted in a high-temperature reactor at 150°C for 8 hours, and the obtained product was centrifuged at 10000 rpm for 10 minutes. The precipitate was taken and washed alternately with anhydrous ethanol and deionized water for 3 times, and vacuum-dried at 60°C to obtain sodium citrate-stabilized hydroxyapatite whiskers. The obtained sodium citrate-stabilized hydroxyapatite whiskers were dispersed in deionized water to prepare a whisker suspension with a mass fraction of 45wt%, and finally a cell disruptor was used to perform ultrasonic treatment at a power of 200W for 10 minutes to obtain sodium citrate-stabilized hydroxyapatite whisker liquid crystals.

[0146] (3) The hydroxyapatite whisker liquid crystal prepared in step (2) is added to the chitin whisker liquid crystal obtained in step (1) at a mass ratio of 1:4 to obtain a mixed system, which is then ultrasonically homogenized at a power of 300 W for 30 minutes using a cell disruptor, and further stabilized at room temperature to obtain a co-assembled liquid crystal.

[0147] The TEMPO oxidized chitosan whiskers prepared in step (1) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 150-350 nm and 15-30 nm, respectively, and had a high aspect ratio. The hydroxyapatite whiskers prepared in step (2) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 45-60 nm and 4-8 nm, respectively, and had a relatively high aspect ratio.

[0148] The zeta potential value of the TEMPO oxidized chitosan whiskers prepared in the above steps was measured by a Zeta potential analyzer: -40.9 mV, and the zeta potential value of the sodium citrate stabilized hydroxyapatite whiskers was: -34.5 mV.

[0149] The co-assembled liquid crystal prepared in step (3) was observed by polarizing microscope. At the mass ratio of the two whiskers, due to the strong negative charge of the two whiskers, the two whiskers in the co-assembled system can still co-assemble to form a liquid crystal phase, showing a good liquid crystal fingerprint texture under polarized light. The results are as follows: Figure 6 As shown in D.

[0150] Example 8

[0151] (1) Preparation of TEMPO-oxidized chitosan whisker liquid crystals: 4.5 g of chitosan was dispersed in 135 mL of deionized water containing 0.072 g of TEMPO and 0.45 g of NaBr at 27°C, and then 15 mL of NaClO solution (active chlorine content: 10%) was added dropwise to obtain a mixed solution; wherein the concentration of TEMPO was 3 mmol / L, the concentration of NaBr was 30 mmol / L, and the concentration of NaClO was 300 mmol / L, and the molar ratio of TEMPO:NaBr:NaClO in the mixed solution was 1:10:100. A 1 mol / L sodium hydroxide solution was continuously added to adjust the reaction pH to 10.0, and the reaction was stirred for 6 hours. After the reaction was completed, 10 to 15 mL of ethanol was added to the reaction solution to quench the reaction. The product was centrifuged at 10,000 rpm for 10 minutes, washed with deionized water, and freeze-dried to obtain TEMPO-oxidized chitosan whiskers. The obtained TEMPO-oxidized chitosan whiskers were then dispersed in deionized water to prepare a whisker suspension with a concentration of 10 wt%. Finally, the suspension was ultrasonically treated with a cell disruptor at a power of 450 W for 1.5 hours to obtain TEMPO-oxidized chitosan whisker liquid crystals.

[0152] (2) Preparation of polyacrylic acid stabilized hydroxyapatite whisker liquid crystals: 1.08 g polyacrylic acid (M w =2000) to obtain a calcium chloride aqueous solution containing polyacrylic acid, wherein the polyacrylic acid and calcium chloride mol ratio is 0.064:1; finally, the calcium chloride aqueous solution containing polyacrylic acid is mixed and stirred with an equal-volume concentration of 0.06mol / L potassium phosphate aqueous solution, wherein the calcium-phosphorus mol ratio in the mixed solution is 1.67, the mixed solution is reacted at 60°C for 48h, the obtained product is centrifuged at 10000rpm for 10min, a precipitate is taken, and the precipitate is washed alternately 3 times with absolute ethanol and deionized water to obtain the desired product, the product is vacuum-dried to obtain polyacrylic acid-stabilized hydroxyapatite whiskers, the obtained polyacrylic acid-stabilized hydroxyapatite whiskers are dispersed in deionized water to prepare a whisker suspension having a mass fraction of 25wt%, and finally a cell disruptor is used to perform an ultrasonic treatment for 10min at 200W power to obtain the polyacrylic acid-stabilized hydroxyapatite whisker liquid crystal.

[0153] (3) The hydroxyapatite whisker liquid crystal prepared in step (2) is added to the chitin whisker liquid crystal obtained in step (1) at a mass ratio of 10:1 to obtain a mixed system, and then ultrasonically homogenized at a power of 300 W using a cell disruptor for 30 minutes, and further stabilized at room temperature to obtain a co-assembled liquid crystal.

[0154] The TEMPO oxidized chitosan whiskers prepared in step (1) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 150-350 nm and 15-30 nm, respectively, and had a high aspect ratio. The hydroxyapatite whiskers prepared in step (2) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 80-120 nm and 16-26 nm, respectively, and had a relatively high aspect ratio.

[0155] The zeta potential value of the TEMPO oxidized chitosan whiskers prepared in the above steps was measured by a Zeta potential analyzer: -45.4 mV, and the zeta potential value of the polyacrylic acid stabilized hydroxyapatite whiskers was: -38.2 mV.

[0156] Example 9

[0157] (1) Preparation of TEMPO-oxidized chitosan whisker liquid crystals: 6 g of chitosan powder was dispersed in 180 mL of deionized water containing 0.096 g of TEMPO and 0.6 g of NaBr at 25°C, and then 20 mL of NaClO solution (active chlorine content: 10%) was added dropwise to obtain a mixed solution; wherein the concentration of TEMPO was 3 mmol / L, the concentration of NaBr was 30 mmol / L, and the concentration of NaClO was 300 mmol / L, and the molar ratio of TEMPO:NaBr:NaClO in the mixed solution was 1:10:100. A 1 mol / L sodium hydroxide solution was continuously added to adjust the reaction pH to 10.0, and the reaction was stirred for 4 hours. After the reaction was completed, 10 to 15 mL of ethanol was added to the reaction solution to quench the reaction. The product was centrifuged at 10,000 rpm for 10 minutes, washed with deionized water, and freeze-dried to obtain TEMPO-oxidized chitosan whiskers. The obtained TEMPO-oxidized chitosan whiskers were then dispersed in deionized water to prepare a whisker suspension with a concentration of 10 wt%. Finally, the suspension was ultrasonically treated with a cell disruptor at a power of 450 W for 1 hour to obtain TEMPO-oxidized chitosan whisker liquid crystals.

[0158] (2) Preparation of polyacrylic acid stabilized hydroxyapatite whisker liquid crystals: 1.44 g polyacrylic acid (M w=2000), wherein the polyacrylic acid and calcium chloride mol ratio is 0.072:1, finally the calcium chloride aqueous solution containing the polyacrylic acid and the isopyknic concentration are mixed and stirred with a 0.09mol / L potassium phosphate aqueous solution to obtain a mixed solution, wherein the calcium-phosphorus mol ratio in the mixed solution is 1.67; the mixed solution is reacted at 70 ℃ for 56h, the product obtained is centrifuged at 10000rpm for 10min, a precipitate is taken, and the required product is obtained after washing 3 times with absolute ethanol and deionized water alternately, the product is vacuum-dried to obtain polyacrylic acid stabilizing hydroxyapatite whiskers, the stabilizing hydroxyapatite whiskers of the polyacrylic acid obtained are dispersed in deionized water, mixed with a whisker suspension having a mass fraction of 10wt%, and finally a cell disruptor is used to carry out ultrasonic treatment for 10min under 200W power to obtain the stabilizing hydroxyapatite whisker liquid crystal of the polyacrylic acid.

[0159] (3) The hydroxyapatite whisker liquid crystal prepared in step (2) is added to the chitin whisker liquid crystal obtained in step (1) at a mass ratio of 1:10 to obtain a mixed system, and then ultrasonically homogenized at a power of 300 W for 25 minutes using a cell disruptor, and further stabilized at room temperature to obtain a co-assembled liquid crystal.

[0160] The TEMPO oxidized chitosan whiskers prepared in step (1) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 150-350 nm and 15-30 nm, respectively, and had a high aspect ratio. The hydroxyapatite whiskers prepared in step (2) were observed under a transmission electron microscope. The length and diameter of the whiskers were mainly concentrated in the range of 80-120 nm and 16-26 nm, respectively, and had a relatively high aspect ratio.

[0161] The zeta potential value of the TEMPO oxidized chitosan whiskers prepared in the above steps was measured by a Zeta potential analyzer: -42.9 mV, and the zeta potential value of the polyacrylic acid stabilized hydroxyapatite whiskers was: -36.7 mV.

[0162] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the scope of protection of the present invention.

Claims

1. A method for preparing hydroxyapatite whisker / chitin whisker co-assembled liquid crystal, characterized in that The steps include: (1) preparing chitosan whiskers into a chitosan whisker suspension, and ultrasonically treating the chitosan whisker suspension to obtain chitosan whisker liquid crystals; (2) preparing hydroxyapatite whiskers into a hydroxyapatite whisker suspension, and ultrasonically treating the hydroxyapatite whisker suspension to obtain hydroxyapatite whisker liquid crystals; (3) adding the hydroxyapatite whisker liquid crystal prepared in step (2) to the chitin whisker liquid crystal obtained in step (1) to obtain a mixed system, and then ultrasonically homogenizing the system and allowing the system to stand to obtain a co-assembled liquid crystal; The chitin whiskers and the hydroxyapatite whiskers have the same electric charge.

2. The method for preparing hydroxyapatite whisker / chitin whisker co-assembled liquid crystal according to claim 1, characterized in that: The chitosan whiskers are chitosan whiskers with a negative zeta potential; The hydroxyapatite whiskers are hydroxyapatite whiskers with negative zeta potential.

3. The method for preparing hydroxyapatite whisker / chitin whisker co-assembled liquid crystal according to claim 2, characterized in that: The chitin whiskers have a zeta potential of -50 to -30 mV. The hydroxyapatite whiskers are hydroxyapatite whiskers with a zeta potential of -45 to -31 mV mV.

4. The method for preparing hydroxyapatite whisker / chitin whisker co-assembled liquid crystal according to claim 3, characterized in that: The chitosan whiskers are at least one of TEMPO (2,2,6,6-tetramethylpiperidinyl oxide) oxidized chitosan whiskers and maleic anhydride chitosan whiskers; The hydroxyapatite whiskers are at least one of sodium citrate-stabilized hydroxyapatite whiskers and polyacrylic acid-stabilized hydroxyapatite whiskers.

5. The method for preparing hydroxyapatite whisker / chitin whisker co-assembled liquid crystal according to claim 1, characterized in that: The TEMPO oxidized chitosan whiskers are prepared by the following steps: dispersing chitosan powder in deionized water containing TEMPO and sodium bromide at 20-30° C., then dropwise adding a sodium hypochlorite solution to obtain a mixed solution A; then adding an alkaline solution to adjust the pH value of the reaction solution to 9.5-10.5, and stirring the reaction; after the reaction is completed, adding ethanol to the reaction solution to quench the reaction, performing solid-liquid separation on the product, and washing the obtained solid with deionized water and freeze-drying to obtain TEMPO oxidized chitosan whiskers; The maleic anhydride chitosan whiskers are prepared by the following steps: heating and melting maleic anhydride at 60-80° C. to obtain a maleic anhydride melt, then adding chitosan powder and stirring uniformly to form a composite suspension, and performing a maleic anhydride esterification reaction under a nitrogen atmosphere; after the reaction, performing solid-liquid separation on the product, washing the obtained solid with deionized water and freeze-drying to obtain maleic anhydride chitosan whiskers; The sodium citrate-stabilized hydroxyapatite whiskers are prepared by the following steps: first, adding a soluble calcium salt and a soluble phosphate salt to deionized water, stirring and mixing them thoroughly to prepare a calcium salt solution and a phosphate salt solution, respectively; then, adding the sodium citrate solution obtained by fully dissolving sodium citrate in deionized water dropwise to the calcium salt solution under stirring conditions, stirring and mixing uniformly, and then adding the phosphate salt solution dropwise thereto, stirring and reacting thoroughly to obtain a precursor solution; reacting the obtained precursor solution at a high temperature of 120 to 180° C. for 3 to 24 hours; separating the obtained product into solid and liquid, washing the obtained solid with anhydrous ethanol and deionized water alternately, and drying to obtain sodium citrate-stabilized hydroxyapatite whiskers; The polyacrylic acid-stabilized hydroxyapatite whiskers are prepared by the following steps: adding polyacrylic acid to a soluble calcium salt aqueous solution, mixing and stirring the calcium salt aqueous solution containing the polyacrylic acid with an equal volume of a soluble phosphate salt aqueous solution to obtain a mixed solution B, wherein the calcium-phosphorus molar ratio in the mixed solution B is controlled to be 1.67; then reacting the mixed solution B at 40-80° C. for 24-72 hours, performing solid-liquid separation, washing the obtained solid with anhydrous ethanol and deionized water alternately, and drying the obtained product to obtain the polyacrylic acid-stabilized hydroxyapatite whiskers.

6. The method for preparing hydroxyapatite whisker / chitin whisker co-assembled liquid crystal according to claim 5, characterized in that: In the preparation of the TEMPO oxidized chitosan whiskers: The chitosan powder is used in a mass ratio of 3:1 to 20:1 with respect to sodium bromide; The concentration of TEMPO in the mixed solution A is 1-6 mmol / L, the concentration of NaBr is 10-60 mmol / L, and the concentration of NaClO is 100-600 mmol / L; the molar ratio of TEMPO:NaBr:NaClO is 1:10:100; The alkaline solution is a sodium hydroxide solution; In the preparation of the maleic anhydride chitosan whiskers: The maleic anhydride is used in a mass ratio of 5:1 to 30:1 to chitin powder; In the preparation of the sodium citrate-stabilized hydroxyapatite whiskers: The soluble calcium salt is at least one of calcium nitrate and calcium chloride; The concentration of the calcium salt solution is 0.1-2 mol / L; The soluble phosphate salt is at least one of trisodium phosphate and potassium phosphate; The concentration of the phosphate solution is 0.1-1 mol / L; The molar ratio of calcium to phosphorus in the precursor solution is 1.67; The concentration of the sodium citrate solution is 0.1-2 mol / L; The molar ratio of the sodium citrate to the soluble calcium salt is 1:6 to 4:3; In the preparation of the polyacrylic acid stabilized hydroxyapatite whiskers: The soluble calcium salt is at least one of calcium nitrate and calcium chloride; The concentration of the calcium salt solution is 0.05-2 mol / L; The soluble phosphate salt is at least one of trisodium phosphate and potassium phosphate; The concentration of the soluble phosphate aqueous solution is 0.05-2 mol / L; The molecular weight of the polyacrylic acid is 1500 to 3000; The molar ratio of the polyacrylic acid to the soluble calcium salt is 0.036:1 to 0.144:1; The concentration of polyacrylic acid in the mixed solution B is 0.36-1.44% by mass volume.

7. The method for preparing hydroxyapatite whisker / chitin whisker co-assembled liquid crystal according to claim 5, characterized in that: In the preparation of the TEMPO oxidized chitosan whiskers: The stirring reaction time is 1 to 7 hours; The amount of ethanol used is calculated based on its volume being 2 to 15% of the volume of the reaction solution; The solid-liquid separation method is centrifugation; In the preparation of the maleic anhydride chitosan whiskers: The esterification reaction is carried out at 100-135° C. for 2-6 hours; The solid-liquid separation method is centrifugation; In the preparation of the sodium citrate-stabilized hydroxyapatite whiskers: The high temperature reaction conditions are 150-160° C. for 6-12 hours; The solid-liquid separation method is centrifugation; The drying method is vacuum drying; In the preparation of the polyacrylic acid stabilized hydroxyapatite whiskers: The reaction conditions of the mixed solution B are as follows: the reaction temperature is 60-70° C. for 48-56 hours; The solid-liquid separation method is centrifugation; The drying method is vacuum drying.

8. The method for preparing hydroxyapatite whisker / chitin whisker co-assembled liquid crystal according to claim 1, characterized in that: The concentration of the chitosan whisker suspension in step (1) is 6 to 15 wt %; The ultrasonic treatment conditions in step (1) are ultrasonic treatment at a power of 300 to 500 W for 1 to 3 hours; The mass fraction of the hydroxyapatite whisker suspension in step (2) is 10 to 60 wt %; The ultrasonic treatment in step (2) is carried out at a power of 100 to 400 W for 3 to 30 minutes. The hydroxyapatite whisker liquid crystal and the chitin whisker liquid crystal described in step (3) are mixed in a mass ratio of 1:30 to 30:1; The ultrasonic homogenization treatment condition described in step (3) is to treat at a power of 150 to 400 W for 15 minutes to 2 hours.

9. A hydroxyapatite whisker / chitin whisker co-assembled liquid crystal, characterized by: It is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the hydroxyapatite whisker / chitin whisker co-assembled liquid crystal according to claim 9 as a biomimetic material.

Citation Information

Cited By

  • Modified chitosan-hydroxyapatite composite material as well as preparation method and application thereof

    CN121891263A